Investigation on mixture design of one-part geopolymer from fly ash and water treatment sludge - Ho, Vuong (Animo Repository, 2022)
This study presents a one-part geopolymer system from coal fly ash and water treatment sludge. Geopolymer is typically produced from two parts namely the aluminosilicate solids, which is typically sourced out from industrial by-product, and an alkali activator solution which reacts with aluminosilicate solids to form an inorganic polymeric network. For a one-part geopolymer system, the solid binder with activators will just be added with water to address the drawback of corrosive and viscous alkali activator solution. Formulation of the proportion of geopolymer precursors with the two solid alkali activators namely sodium hydroxide and sodium aluminate was conducted using statistical mixture design. Effects of each components as well as interactions between them were evaluated by step-wise regression analysis. It was found that high alkali content decreased the compressive strength of binder. Meanwhile, the incorporation of sludge in this system helps reduce the unit weight of samples. Multiple response surface analysis that maximized compressive strength and minimized unit weight resulted in the optimal combination of 18.9% sludge, 76.1% fly ash and 5.0% NaOH. © The Authors, published by EDP Sciences, 2018.